Islamic Education Management Strategy through Optimizing Facilities and Infrastructure Financing to Improve the Quality of Learning - sabila, jihan prisilia; Kholis P., Muhammad Nur; Dwiqi M., Ahmad; Alifiya, Aida; Ta’rifin, Ahmad (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
Educational facilities and infrastructure are important factors in improving the efficiency of learning and learning. Management of educational facilities and infrastructure is defined as a collaborative process of the effective and efficient utilization of all educational facilities and infrastructure. The purpose of managing educational facilities and infrastructure is to provide professional services in the field of educational facilities and infrastructure to carry out the education process effectively and efficiently. This qualitative research aims to reveal the implementation of management of education facilities and infrastructure and the role of teachers in improving the quality of learning through the utilization of educational facilities and infrastructure at SMP N 2 Kajen Pekalongan, by way of interviews, observation, and documentation. The data validity technique uses triangulation to make the data obtained more accurate.